Effects of trazodone administration on the neurologic examination in healthy dogs - Lizabeth C. Lueck; Starr Cameron; Natalia Zidan (Journal of Veterinary Internal Medicine, 2022)
Abstract Background Trazodone is an anxiolytic used PO to decrease anxiety in dogs. Whether or not trazodone affects the neurologic examination in dogs has not been previously reported. Objective Investigate whether trazodone administration is associated with changes in the neurologic examination in healthy dogs. Animals Thirty‐two healthy dogs between 1 and 6 years old with no previously diagnosed medical conditions and perceived by their owners as neurologically normal. Methods Baseline sedation and anxiety assessments and neurologic examination were performed on each dog, followed by trazodone administration (6.25‐8.60 mg/kg PO). The sedation and anxiety assessments and neurologic examination were repeated 2.5 hours after trazodone administration. The examinations were performed by a single board‐certified veterinary neurologist and were video‐recorded. The videos were randomized and reviewed by a different neurologist, blinded to the previous evaluations, who scored the examinations. Results Seven of 32 (22%) dogs had worse scores on their neurologic examination after receiving trazodone, manifesting as new or progressive PR deficits. Although not clinically relevant, 18.7% of the dogs had consciousness levels that changed from bright, alert, responsive to quiet, alert, responsive after trazodone administration. No other changes were observed on neurologic examination. Sedation and anxiety scores were significantly different after trazodone administration compared to before (P < .001 and P < .001, respectively). Conclusions and Clinical Importance Most dogs did not have changes on neurologic examination after trazodone administration. However, approximately 20% of dogs had new or worsening PR deficits after receiving trazodone. Ideally, trazodone should not be given before neurologic examination in dogs.